2021
DOI: 10.1183/13993003.03633-2020
|View full text |Cite
|
Sign up to set email alerts
|

Intake of n-3 polyunsaturated fatty acids in childhood, FADS genotype and incident asthma

Abstract: Longitudinal evidence on the relation between dietary intake of n-3 (omega-3) very long-chain polyunsaturated fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), in mid-childhood and asthma risk is scarce. We aimed to investigate whether a higher intake of EPA and DHA from fish in childhood is associated with a lower risk of incident asthma.In the Avon Longitudinal Study of Parents and Children, dietary intakes of EPA and DHA from fish were estimated by food frequency questionnaire at 7 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Among them, n-3 and n-6 PUFAs possess important physiological functions [ 13 , 14 ]. The change of the n-3/n-6 LC-PUFA ratio in the diet, especially the increased consumption of n-6 LC-PUFA and the decreased consumption of n-3 LC-PUFA, are considered to be linked with an increased risk of asthma or wheeze [ 15 17 ]. In many countries, high consumption of vegetable oils and meat has increased the intake of n-6 LC-PUFA and arachidonic acid (AA, 20:4, n-6), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, n-3 and n-6 PUFAs possess important physiological functions [ 13 , 14 ]. The change of the n-3/n-6 LC-PUFA ratio in the diet, especially the increased consumption of n-6 LC-PUFA and the decreased consumption of n-3 LC-PUFA, are considered to be linked with an increased risk of asthma or wheeze [ 15 17 ]. In many countries, high consumption of vegetable oils and meat has increased the intake of n-6 LC-PUFA and arachidonic acid (AA, 20:4, n-6), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, DHA and EPA are precursors for protectins and resolvins, which bring about a programmed resolution of the inflammatory process 50 51. Observational studies and randomised controlled trials have also shown a protective effect of PUFAs on asthma development52–54—for example, an inverse association of plasma PUFA levels and dietary PUFA intake with the risk of allergic sensitisation and asthma-like symptoms at age 3 years 52. Supplementation with ω−3 long-chain PUFAs during the third trimester of pregnancy significantly reduced the risk of persistent wheeze or asthma in offspring 53.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, there were no consistent differences in the observed association related to gender, allergic sensitization, or FADS genotype. One recent longitudinal study on dietary VLC n–3 PUFAs from fish intake however observed a significant inverse association with incident asthma up to adolescence only among the minor allele G carriers of the FADS gene, associated with lower plasma concentrations of VLC n–3 PUFAs ( 17 ). Similar results were observed in a randomized trial on fish oil supplementation in pregnancy, where the strongest effect of supplementation in relation to childhood asthma was observed in children of mothers carrying the same FADS gene variant ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal analyses from the Barn, Allergi, Miljö, Stockholm, Epidemiologi (BAMSE) birth cohort have previously shown that regular intake of fish in infancy, as well as biomarkers of fish intake at school age, can reduce the risk of allergic disease including asthma ≤12 and ≤16 y of age, respectively ( 11 , 16 ). In addition, a recent study based on the UK Avon Longitudinal Study of Parents and Children (ALSPAC) birth cohort, with replication in the BAMSE birth cohort, found that this association may be modified by fatty acid desaturase ( FADS ) genotype ( 17 ). The results showed that higher intake of the VLC n–3 PUFAs EPA (20:5n–3) and DHA (22:6n–3) from fish in childhood was inversely associated with incident asthma up to adolescence only among participants with a common genetic variant (minor G allele), which has previously been associated with lower plasma concentrations of VLC n–3 PUFAs ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation